2023
DOI: 10.1097/ms9.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of cystic artery, cystic duct, and gall bladder and their associated intraoperative and postoperative complications: an observational study

Abstract: Background: Anatomical variations in the calots triangle encountered during laparoscopic cholecystectomy are not uncommon. Misidentification and misperception of these structures are the major cause of vasculobiliary injuries. This study was conducted to estimate the prevalence of anatomical variations of the cystic artery, cystic duct (CD), and gall bladder. This is the first study in India to access the rate of intraoperative and postoperative complications in anatomical variants compared to norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Gallbladder Anomalies Common hepatic artery anomalies (8.39%) followed by cystic duct anomalies (3.49%) right hepatic duct anomaly (2.79%), gall bladder anomalies (2.9%), and least common was presence of common hepatic artery (1.39%). Consistently Gupta R et al 22 reported that the most common variations were found in cystic arteries, accounting for 16.8% of cases. Anomalies in the CD were detected in 11.4% of cases, while anomalies in the gall bladder were the least frequent, occurring in only 5.4% of cases.…”
Section: Cystic Artery Anomalies Cystic Duct Anomalies Right Hepatic ...supporting
confidence: 67%
“…Gallbladder Anomalies Common hepatic artery anomalies (8.39%) followed by cystic duct anomalies (3.49%) right hepatic duct anomaly (2.79%), gall bladder anomalies (2.9%), and least common was presence of common hepatic artery (1.39%). Consistently Gupta R et al 22 reported that the most common variations were found in cystic arteries, accounting for 16.8% of cases. Anomalies in the CD were detected in 11.4% of cases, while anomalies in the gall bladder were the least frequent, occurring in only 5.4% of cases.…”
Section: Cystic Artery Anomalies Cystic Duct Anomalies Right Hepatic ...supporting
confidence: 67%
“…Among these variations, the presence of Luschka ducts, also known as subvesical ducts, alongside an aberrant right hepatic duct, represents a particularly infrequent occurrence [2]. This unique combination presents a surgical conundrum and is an important risk factor for biliary surgical lesions during cholecystectomy [3].…”
Section: Introductionmentioning
confidence: 99%
“…During this procedure, an anatomical anomaly was discovered, consisting of a 3 mm aberrant right hepatic duct draining into the cystic duct, accompanied by three 1 mm subvesicular ducts connecting to the common hepatic duct. A thorough understanding of anatomical variations is essential for assessing the practicality of surgical procedures and executing surgeries in this area without complications [3].…”
Section: Introductionmentioning
confidence: 99%